Effect of intrauterine and oral therapy during periparturient period in sow - SINGH, N K; SINGH, BALRAJ; SINHA, A K; SINGH, M P; SINGH, S K (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on 73 sows of T x D (Tamworth x Desi) breed. The sows were attotted under six groups and various treatment viz. Gestaforte vet bolus (group T1), uterotone and (group T"), both orally and Betadine liquid intrauterine along with payapro bolus orally (group T3), and only Betadine liquid intrauterine (group T) were initiated within 24 hours of farrowing. Two groups (group C1 and C) were kept as control. Significantly (P<0.05) higher weight was recorded in piglets of sows treated with Gastaforte vet bolus (group T1) and uterotone liquid (group T,). Litter weight also increased significantly (P<0.05) at different ages of piglets belonging to the sows of above two treated groups. Average post weaning fertile estrus was found shortest in sows belonging to intrauterine medication groups, though the effect of treatment on the interval of fertile estrus was non-significant.